The Effect of International Sanctions on the Size of the Middle Class in Iran - Mohammad Reza Farzanegan; Nader Habibi (CESifo GmbH, 2024)
This study examines the impact of international economic sanctions, imposed on Iran due to its nuclear program, on the development of the middle class. Specifically, it investigates how the middle class in Iran would have developed in the absence of these sanctions post-2012. To address this question, we employ a synthetic control model to create a counterfactual scenario for Iran, using a weighted average of other comparable countries that mirror pre-sanction Iran, but did not experience significant international sanctions. By comparing the middle-class size of this counterfactual Iran with the actual Iran that faced major economic sanctions, our results indicate that the annual middle-class size would have been approximately 11 percentage points larger, on average, without the post-2012 sanctions. Our findings are robust across various tests, including placebo tests and synthetic difference-in-difference analyses. The latter analysis shows that the estimated average effect of sanctions on the middle-class size of Iran from 2012 to 2019 is highly statistically significant. Finally, we provide evidence on the relevance of real GDP per capita and merchandise imports as key selected channels through which sanctions negatively affect the size of the middle class.
Keywords: F51; I31; P36; 330; sanctions; Iran; middle class; poverty; inequality; synthetic control method; counterfactual